Sometimes more competent, but always less warm: Perceptions of biologically oriented mental-health clinicians. (November 2015) - Lebowitz, Matthew S; Ahn, Woo-kyoung; Oltman, Kathleen
Background and aims: Biological conceptualizations of psychopathology are ascendant, including among mental-health clinicians. However, it is unknown how this might affect people's perceptions of clinicians, which in turn could have considerable public-health implications. The present studies sought to address this issue. Methods: In the present research, participants imagined that they or their loved ones were suffering from a mental disorder and then rated their perceptions of one clinician espousing the view that 'mental disorders are brain diseases' and another describing them as 'disorders of thoughts and emotions'. Results: Biologically oriented clinicians were perceived as more competent and effective only when the disorder in question was judged to be biologically caused. Otherwise, there was no significant difference in perceived competence, and biologically oriented clinicians were rated less effective. Regardless, all participants perceived the biologically oriented clinician as significantly less warm on average than the psychosocially oriented clinician. Conclusion: These findings may have important clinical implications for the crucial therapeutic alliance between therapists and patients.